SIMULATION FOR THE CONTROL OF A LINEAR INDUCTION MOTOR WITH END EFFECT FED BY MATRIX CONVERTER - Altun, Huseyin (Gazi Univ, Fac Engineering Architecture, 2011)
In this study, simulation of field-oriented control of a linear induction motor fed by matrix converter was conducted. End-effect in the linear induction motor which occurs due to the structure has been taken into consideration. The matrix converter and the linear induction motor with end-effect have been modelled in Matlab/Simulink. With the constructed simulation model and because end-effect in the linear induction motor has been taken into account, results in accordance with actual conditions have been obtained. Use of matrix converter in the linear induction motor drive system has brought advantages of the matrix converter to the drive system. Negative reflection of the end-effect to the performance of vector control, in a conventional manner, of the linear induction motor has been shown by the obtained results. Subsequently, this negative reflection has been compensated with a new approach to improve the control performance, and for both cases results were given in comparison. The results demonstrate the effectiveness of the proposed control technique.
Keywords: Linear induction motor; end-effect; matrix converter; field-oriented control